Beneficial traits of root endophytes and rhizobacteria associated with plants growing in phytomanaged soils with mixed trace metal-polycyclic aromatic hydrocarbon contamination. (August 2021) - Kidd, Petra S.; Álvarez, Analía; Álvarez-López, Vanessa; Cerdeira-Pérez, Andrea; Rodríguez-Garrido, Beatriz; Prieto-Fernández, Ángeles; Chalot, Michel
Abstract: The diversity of cultivable bacteria associated with plants from phytomanaged soils with mixed trace metal (TM) and polycyclic aromatic hydrocarbon (PAH) contamination in Pierrelaye (France) was evaluated. The emphasis was on the cultivable bacterial community since the overall objective is to obtain inoculants to improve the remediation of this type of contaminated site. Root endophytic and rhizosphere soil bacterial counts were determined, and isolates were pooled by amplified rDNA restriction analysis and identified by 16S rDNA sequencing. Isolates were further characterized for the production of plant growth-promoting (PGP) substances, and resistance to TM. The selected strains were evaluated for their ability to degrade PAHs. The potential of cell-free microbial supernatant to increase the mobilisation of PAHs from the polluted soil of Pierrelaye was also evaluated. Proteobacteria and Actinobacteria dominated the collection of isolates, and differences in taxonomic diversity were observed between plant species ( Populus or Zea mays ) and depending on the remediation treatment ( Populus inoculation with mycorrhizae or Populus intercropping with Alnus ). The majority of isolates exhibited at least one of the tested PGP traits, as well as resistance to more than one TM. Several rhizosphere, endophyte and even one bulk soil isolate showed high rates of fluoranthene and pyrene reduction. The endophyte Rhizobium strain MR28 isolated from maize and degrading pyrene produced bioemulsifying molecules capable of improving the availability of PAHs from the soil of Pierrelaye. A selection of the most interesting strains was made for further re-inoculation experiments in order to assess their potential in rhizoremediation processes. Highlights: Inoculants can improve the remediation of trace metals and PAHs from soil. Plant-associated bacteria from phytomanaged contaminated soils were studied. Proteobacteria and Actinobacteria dominated the collection of isolates. Rhizosphere, endophyte, and bulk soil strains reduced fluoranthene and pyrene. The cell-free supernatant of an endophyte strain improved the availability of PAHs.